Study skills for academic writing. - Trzeciak, John (English for academic study, 1994)
Designed for upper-intermediate/advanced English language learners, this course aims to enable students to use written sources wisely in their academic essays, reports and dissertations. It advises how to incorporate ideas into their own written work: summarizing, assessing and avoiding plagiarism.